Design of a Glycoconjugate Vaccine Against Salmonella Paratyphi A - Renzo Alfini; Martina Carducci; Luisa Massai; Daniele De Simone; Marco Mariti; Omar Rossi; Simona Rondini; Francesca Micoli; Carlo Giannelli (Vaccines)
Background/Objectives: Typhoid and paratyphoid fever together are responsible for millions of cases and thousands of deaths per year, most of which occur in children in South and Southeast Asia. While typhoid conjugate vaccines (TCVs) are licensed, no vaccines are currently available against S. Paratyphi A. Here we describe the design of a S. Paratyphi A conjugate. Methods: The serovar-specific O-antigen (O:2) was linked to the CRM197 carrier protein (O:2–CRM197) and a panel of conjugates differing for structural characteristics were compared in mice and rabbits. Results: We identified the O-antigen molecular size, polysaccharide to protein ratio, conjugate cross-linking, and O:2 O-acetylation level as critical quality attributes and identified optimal design for a more immunogenic vaccine. Conclusions: This work guides the development of the O:2–CRM197 conjugate to be combined with TCV in a bivalent formulation against enteric fever.